The Menzerath-Altmann Law and Sentence Structure. Issue 3 (2nd July 2016) - Sanada, Haruko
Abstract: The present study investigates three relationships with respect to their agreement with the Menzerath-Altmann law on data from Japanese: (1) Sentence length and clause length, (2) clause length and argument length, and (3) sentence length and argument length. The data supports Hypotheses (1) and (3), whereas (2) is not supported. Possible reasons for this result are discussed. Moreover, the influence of sentence structure on the relationships will be investigated with reference to the following aspects: The type of arguments of the individual verb, the depth of the clause, the length of the embedding clause, and the order of arguments in the clause.